Manitoba politics and government : issues, institutions, traditions - Thomas, Paul G. (University of Manitoba Press, 2010)
Manitoba Politics and Government is a rich and fascinating account of a province that strives for the centre, for the delicate middle ground where individualism and collectivism overlap, and where a multitude of different cultures and traditions create a highly balanced society."--Pub. desc.